A gramática no ensino fundamental: orientações, usos e possibilidades - Silva, Rosa Cristina da (2024)
This research was done for the Federal University of Uberlândia's (UFU) Postgraduate Professional Master's Program in Modern Languages, under the theme "Grammar and Teaching", in order to discuss grammar as a teaching tool and as an instrument. The study's historical trajectory, origin, and development are briefly traced, along with the object's evolution in Brazil and the grammatization process, which consists of describing and instrumenting a language through two technologies that underpin knowledge: grammar and dictionaries. The study's objectives are to create a teaching proposal that invites critical thinking about grammar, its social function, and its application to the teaching of Portuguese, as well as to create a grammatical teaching methodology that complies with official guidelines, such as the National Common Curricular Base (BNCC) (Brazil, 2018) and the Curricular Document for Goiás (DC-GO – Expanded) (Goiás, 2018). The analyses center on the application of grammar in the classroom and the significance of this didactic-pedagogical tool for the instruction of Portuguese language users and speakers, particularly for the development of writing skills and practice speaking in various communicative contexts, though talks about the idea, purpose, and specially, the application of grammar to enhance and comprehend the way language functions. In order to achieve this, a set of workshops are provided to ninth-grade elementary school students at a state school in Quirinópolis, GO. These workshops guide the use of grammar in the classroom and explore resources beyond the simple explanation of rules, terminologies, and nomenclatures. The goal is to foster curiosity about research, the growth of academic independence and critical thinking, and the recognition that the use of this pedagogical material is crucial for the process of teaching and learning about the mother language in the classroom. The study focuses on theoretical contributions on the usage of grammar made by a number of authors, including Antunes (2007), Travaglia (2009), Bagno (2000, 2012), and Neves (2002, 2014). The educational proposal, which adopts Travaglia's viewpoint, centers on teaching usage, reflective, theoretical, and normative grammar. We begin by conducting preliminary bibliographical study on the subject. A subsequent action research study based on a didactic suggestion enables us to reassess grammar's role in instruction. The collected data were examined, evaluated, and given a qualitative description. This work is expected to contribute to a review of the importance of grammar in student education, as well as to dispel some myths about this instrument. The obtained data was analyzed, interpreted and described qualitatively. The applications of the activities in form of a workshop in our didactic proposal gave our students the opportunity of bigger interactions in classroom, allowing considerable development in relation of speaking, writing, argumentation and reflection about the use of native language. This grants us to conclude that the teaching of grammar focused in the use of grammar, reflexive grammar, theoretical grammar, and normative grammar contribute to a more efficient learning and with relevant meanings, allowing to participating students, another point of view about the study object. We certified that in addition to helping in the formation of a more competent and skilled user, the lesson became more closer to reality, less superficial and meaningless. We also noticed that this format may work and bring satisfactory results related to other aspects (contents of grammar aspects of the Portuguese language). We judged that the activities notebook contemplating the four grammatical types presented in the end of this work, may help the teacher in classroom. That said, we judged that our research collaborates for a revision about materiality grammar for the student’s formation, as well as for the rupture of some preconcepts correlated to this instrument.